Immunoregulatory functions of VISTA. Issue 1 (March 2017) - Nowak, Elizabeth C.; Lines, J. Louise; Varn, Frederick S.; Deng, Jie; Sarde, Aurelien; Mabaera, Rodwell; Kuta, Anna; Le Mercier, Isabelle; Cheng, Chao; Noelle, Randolph J.
Summary: Utilization of negative checkpoint regulators (NCRs) for cancer immunotherapy has garnered significant interest with the completion of clinical trials demonstrating efficacy. While the results of monotherapy treatments are compelling, there is increasing emphasis on combination treatments in an effort to increase response rates to treatment. One of the most recently discovered NCRs is VISTA (V‐domain Ig‐containing Suppressor of T cell Activation). In this review, we describe the functions of this molecule in the context of cancer immunotherapy. We also discuss factors that may influence the use of anti‐VISTA antibody in combination therapy and how genomic analysis may assist in providing indications for treatment.